2021
DOI: 10.1038/s41598-021-85587-7
|View full text |Cite
|
Sign up to set email alerts
|

Microsomic and macrosomic body structure in children and adolescents affected by syndromes or diseases associated with neurodysfunction

Abstract: In Poland the issue of microsomic body structure (micro-SBS) and macrosomic body structure (macro-SBS) has so far been overlooked. Up until now only a small amount of data have been published, most often as an overview of the problem. The current study was designed to investigate the co-occurrence of microsomic/macrosomic body structure (micro/macro-SBS) and congenital nervous system disorders or neurological syndromes with symptoms visible from infancy, based on essential data acquired during admission proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…The division of the examined group of children and adolescents with neurodysfunction into subgroups proposed by the authors has already been presented [ 15 , 24 , 40 , 41 ]. It is important from a methodological point of view because it allowed to show statistically significant relationships within the specified subgroups, such as, for example, spastic CP [ 15 , 24 ]; NTDs or between subgroups, for example, such as NTDs; NMD out of seven subgroups [ 24 , 40 ]; and NPE out of three subgroups [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The division of the examined group of children and adolescents with neurodysfunction into subgroups proposed by the authors has already been presented [ 15 , 24 , 40 , 41 ]. It is important from a methodological point of view because it allowed to show statistically significant relationships within the specified subgroups, such as, for example, spastic CP [ 15 , 24 ]; NTDs or between subgroups, for example, such as NTDs; NMD out of seven subgroups [ 24 , 40 ]; and NPE out of three subgroups [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also important to consider the coexistence of hypothyroidism and epilepsy [ 15 , 24 , 40 ]. The following developmental disorders were examined in the described group and subgroups: microcephaly and macrocephaly [ 40 ], relative/absolute microcephaly and relative/absolute macrocephaly [ 24 ], short stature and tall stature [ 40 ], microsomia and macrosomia [ 41 ]. Eating disorders have not been presented so far.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, growth disorders may be reflected by two opposing conditions: short stature and tall stature [11][12][13]. Based on the assessment of the varied weight-height ratios, it is possible to evaluate the nutritional status [14][15][16]. In clinical conditions and scientific research, different definitions of somatic development disorders and various biological reference systems, or reference values, are intentionally used [7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the assessment of the varied weight-height ratios, it is possible to evaluate the nutritional status [14][15][16]. In clinical conditions and scientific research, different definitions of somatic development disorders and various biological reference systems, or reference values, are intentionally used [7][8][9][10][11][12][13][14][15][16][17][18][19]. The present study was designed as a continuation of previously reported research focusing on somatic development disorders in a group of children and adolescents with neurodysfunction [9][10][11]15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation